PEMANFAATAN METODE HEURISTIK TRAVELLING SALESMAN PROBLEM WITH TIME WINDOWS PADA RUTE ANTAR JEMPUT LAUNDRY DENGAN ALGORITMA GENETIKA - Wiwi Widayani; Dhimas Abdi Pratama; Ryan Dhea Pratama; Edy Tama Kusumajaya; Albiruni Dharma (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2019)
Laundry business is quite a lot to bring profit, became main attraction of every person to open this business. Needed innovation in order to improve the service can make customer did not move to another. An example is laundry pickup service optimization where each customer has reserved time to deliver and receive their order. Calculation the fastest route is most important part in serving all customers. Another things is traveling salesman problem (TSP) which goal is to choose the shortest path. In this case, the precise arrival time each customer must be considered. The best solution to the problem is achieved by combining chromosomes(solutions) to produce new chromosome using genetic algorithms(Selection, Crossover and Mutation). Looking for the best solution used several combination of crossover and mutation and size, including population size and generation size. From the test result obtained an optimal value is 2000 with the best crossover and mutation probability is 0,4 and 0,6. From parameter value that can give solutions to serve customers with a time window.